A statistical comparison of accelerated concrete testing methods. Issue 2 (1997) - Meyer, Denny
Abstract : Accelerated curing results, obtained after only 24 hours, are used to predict the 28 day strength of concrete. Various accelerated curing methods are available. Two of these methods are compared in relation to the accuracy of their predictions and the stability of the relationship between their 24 hour and 28 day concrete strength. The results suggest that Warm Water accelerated curing is preferable to Hot Water accelerated curing of concrete. In addition, some other methods for improving the accuracy of predictions of 28 day strengths are suggested. In particular the frequency at which it is necessary to recalibrate the prediction equation is considered.